RARE EARTH EVIDENCE FOR THE ORIGIN OF GNEISSES AROUND YARI BORI AND TSIGA AREA, PARTS OF MALUMFASHI SCHIST BELT, NIGERIA. - S.M. Elatikpo; A.K. Sallau; M.S. Adamu; A.K. Amuda (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
There is variability in the total Rare Earth Elements (REEs) abundance, their distribution patterns and degree of fractionation in the gneisses of Yari Bori and Tsiga area parts of Malumfashi schist belt of Nigeria. The variety of gneisses mapped includes granite gneisses, augen gneisses and the banded gneisses. Most of the gneisses investigated shows marked negative Eu anomalies. Also the REE distribution patterns are significantly fractionated with strong light REE enrichment (La, Ce, Pr, Nd, Sm and Gd,) and heavy REE depletion (Tb, Dy, Ho, Er, Tm, Yb, Lu); a suggestive of melt equilibration with residual garnet. La is in the range of 10.7-81.5 ppm, Ce (21.6-174.6 ppm) and Pr (2.39-20.29 ppm) while Tm is in the range of 0.05-0.73 ppm, Yb (0.30-4.62 ppm) and Lu (0.04-0.67 ppm). The gneisses of this area are interpreted as resulting from magmatic origin involving varying degree of partial melting of lower crust at different depths.